(untitled) (Ameghiniana, 2014)
"Specimens of Polyschides tetraschistus (Watson) from sediments referred to the Late Pleistocene are described. This record is the first mention of the Family Cadulidae for that age in Argentina. Polyschides tetraschistus is living today in the area but was not found in Holocene deposits. The occurrence increases the geographic distribution of fossil Cadulidae."